Induction of RAGE-NFkB signalling axis enhances SHP-2 tyrosine phosphatase expression resulting in deviant activation of diabetic monocytes. (14th October 2021) - Dorenkamp, M; Nasiry, M; Koch, S; Reinecke, H; Godfrey, R
Abstract: Purpose: Aberrant activation of Type 2 Diabetes mellitus (T2DM) monocytes is an important pathomechanism leading to restricted arteriogenesis and augmented atherosclerosis, hereby, accelerating CAD and PAD. Tyrosine phosphatase SHP-2 was found to be upregulated in T2DM-monocytes. This study aimed to identify the pathways regulating SHP-2 expression in T2DM-monocytes. Methods: Primary human monocytes were isolated from the peripheral blood of T2DM patients and healthy individuals. Monocytes were incubated with Methylglyoxal (MG), a highly reactive side product of glycolysis, Receptor for advanced glycation end product (RAGE) ligand AGE-bovine serum (AGE-BSA) or TNFα for 24 hours. Transwell migration assays were used to analyse the migratory potential of monocytes. Western Blot, RT-qPCR and FACS were performed to quantify the expression of relevant molecules. Pharmacological inhibitors were used to study functional relevance of the RAGE-NFκB-SHP-2 signalling axis. Results: Significantly enhanced SHP-2 expression was detected in monocytes, which were incubated with TNFα, MG or AGE-BSA, respectively. Co-incubation of these molecules with NFκB-inhibitor blocked SHP-2 upregulation. Pharmacological inhibition of RAGE reversed the MG or AGE-BSA induced SHP-2 expression and activity in monocytes. RAGE expression on monocytes was upregulated after the incubation with MG or AGE-BSA, consistent with enhanced RAGE mRNA levels in T2DM monocytes. Besides, we also detected elevated SHP-2 transcripts in monocytes of T2DM patients which was more pronounced in monocytes with augmented TNFα expression. Furthermore, MG and AGE-BSA provoked the enhanced migration of monocytes which could be significantly reduced after the application of an allosteric SHP-2 inhibitor. Interestingly, pharmacological inhibition of RAGE in these conditions alone was sufficient to block the elevated monocyte migration. Moreover, monocytes isolated from T2DM patients revealed a comparable pro-migratory phenotype, which was completely restored after the pharmacological inhibition of SHP-2. Conclusions: This study identified the upstream signalling mediators that contribute to SHP-2 dependent monocyte activation in T2DM conditions. Glucose metabolite (MG) or RAGE ligand (AGE-BSA) alone were sufficient to induce a pro-migratory phenotype in monocytes by upregulating SHP-2. Of note, an inflammatory state seems to accelerate this effect since enhanced TNFα levels were found to be positively correlated with the augmented SHP-2 expression. Moreover, we identified the RAGE-NFκB signalling axis through which the SHP-2 upregulation is conveyed when augmented accumulation of glucose metabolites occur. These findings reveal a basis for potential new therapeutic approaches to prevent accelerated CAD and PAD in diabetic patients since independent pharmacological inhibition of every step in the RAGE-NFκB-SHP-2 axis was sufficient to reset the aberrant monocyte activation. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Interdisciplinary Center for Clinical Research of the Medical Faculty of the University of Münster